Associations between the muscle quality index and adult lung functions from NHANES 2011–2012 - Weng, Luoqi; Xu, Zhixiao; Chen, Yuhan; Chen, Chengshui (Frontiers in Public Health, 2023)
Background: The muscle quality index (MQI), as an important component of sarcopenia, is defined as the ratio of muscle strength to muscle mass. Lung function, is a clinical indicator to assess ventilation and air exchange function. This study investigated the relationship between lung function indices and MQI in the NHANES database from 2011-2012. Methods: This study included 1558 adults from the National Health and Nutrition Examination Survey from 2011 to 2012. Muscle mass and muscle strength were assessed using DXA and handgrip strength, and all participants underwent pulmonary function measurements. Multiple linear regression and multivariable logistic regression were used to assess the correlation between the MQI and lung function indices. Results: In the adjusted model, MQI was significantly correlated with FVC% and PEF%. And, after quartiles of MQI in Q3, where FEV1%, FVC%, and PEF% were all associated with MQI, in Q4, a lower relative risk of a restrictive spirometry pattern was linked to increased MQI. Compared to the other two age groups, the relationship between the MQI and lung function indices was more significant in the higher age group. Conclusion: There was an association between the MQI and lung function indices. Furthermore, in the middle-aged and elderly population, lung function indicators and restrictive ventilation impairment were significantly associated with MQI. This implies that improving lung function through muscle training may be beneficial to this group.